Children's perceptions of physical literacy: exploring meaning, value, and capabilities for lifelong physical activity - Bingham, Daniel D.; Morris, Jade L.; Lewis, Kiara; Foweather, Lawrence; Goss, Hannah; O’Brien, Wesley; Essiet, Inimfon; Roberts, William M.; Hurter, Liezel; Shearer, Cara; Barnett, Lisa M.; Duncan, Michael J.; et al. (Frontiers in Sports and Active Living, 2025)
IntroductionThe concept of physical literacy has been defined differently across the world. To create a consensus statement and definition of physical literacy for England, it was felt important to incorporate the views and opinions of children and young people who are often the focus of interventions to increase physical activity and physical literacy. The aim of this qualitative study was to understand what physical literacy means to children by exploring their perceptions of meaningful physical activity and what they think will be needed to continue to be active for life.MethodsThrough a series of directed tasks and thematic analysis, several important considerations are discussed. These included the pertinence of social relationships-whether it was to share experiences, support and encourage friends, or learn from your family.Results and DiscussionChildren discussed how physical activity positively affects their emotions and the importance of enjoyment in continuing to engage in movement for the rest of their lives. In addition, there was an awareness of the benefits for mental and physical health, which indicated the prominence of knowing these benefits in engaging. The findings offer some important contributions from children to better understand what physical literacy means in England.